Effects of summer weather and heatwaves on wild boar activity - Güldenpfennig, Justine; Fattorini, Niccolò; Ježek, Miloš; Morelle, Kevin; Podgórski, Tomasz (Royal Society open science, 2025)
Climate change threatens wildlife species, negatively affecting their fitness through environmental change, such as through increased severity of droughts and summer heatwaves. Wild boar (Sus scrofa), a species with limited physiological thermoregulation abilities, is potentially vulnerable to high temperatures during summer. Yet little is known about the behavioural reactions of this species to heat stress. Detailed understanding of wild boar behavioural adaptations to their environment might help understand their future population growth and change in the geographical range. We used multisensory collars on 24 individual wild boars in the Czech Republic, calculating the dynamic body acceleration as a proxy for energy expenditure to detect activity changes in response to high temperatures on two temporal scales (daily and seasonal) and during heatwaves. Our results revealed that overall, under higher temperatures, wild boars reduce their activity, unless it rained. Heatwave duration did not affect wild boar activity. We show that wild boars adapt their activity to weather conditions and highlight the importance of sufficient precipitation for thermoregulation in this species. This suggests that studies about climate change impacts on wildlife behaviour should consider not only rising temperatures but also shifts in rainfall patterns. Additionally, this research shows the potential of remote-sensing technologies to monitor wildlife behaviour, particularly in challenging observational scenarios, offering valuable insights into the behavioural responses of wildlife in the face of a changing climate.
Keywords: heat; biologging; climate change; behaviour; Sus scrofa; telemetry